The Fast-Acting Inhibitor of Tissue-Type Plasminogen Activator in Plasma Is also the Primary Plasma Inhibitor of Urokinase - Kruithof, Egbert K.O; Tran-Thang, Chiên; Bachmann, Fedor (Thrombosis and Haemostasis, 1986)
We have compared the ability of a plasminogen activator inhibitor (PA-inhibitor) in human plasma, to form complexes with radioiodinated tissue-type plasminogen activator (t-PA) and high molecular weight urokinase (HMr-UK). Addition of 125I-t-PA (final concentration 10 IU/ml) or of 125I-HMr-UK (2 IU/ml) to a plasma containing 33 U/ml of PA-inhibitor resulted in the rapid formation of a 110,000 Mr complex of 125I-t-PA or a 95,000 Mr complex of 125I-HMr-UK with PA-inhibitor. Upon prolonged incubation of the plasma with 125I-HMr-UK a secondary complex of a Mr of 88,000 was observed, which probably derives from limited degradation of the 95,000 complex. Preincubation of the plasma with unlabelled t-PA, HMr-UK or LMr-UK at higher concentrations prevented the subsequent formation of complexes between radiolabelled PAs and the PA-inhibitor. These results thus demonstrate that t-PA and UK form complexes with the same PA-inhibitor. The rate of complex formation of 125I-t-PA or of 125I-HMr-UK with the plasma PA-inhibitor was similar (second order rate constant of association with PA-inhibitor in the order of 107 M−1s−1).
Keywords: Plasminogen activator inhibitor; Tissue-type plasminogen activator; Urokinase; PA-inhibitor, t-PA, UK